Competing Bilingual Schools in La Mancha City: Teachers' Responses to Neoliberal Language Policy and CLIL Practices - Ana María Relaño Pastor; Alicia Fernández Barrera (FahrenHouse, 2018)
This article analyzes how neoliberalism as ideology and practice permeates CLIL-type bilingual education teachers' narratives collected as part of the sociolinguistic ethnography conducted in four Spanish-English bilingual schools in La Mancha City (pseudonym). The rapid implementation of Spanish-English bilingual programs in Castilla-La Mancha schools in the last decade (e.g. «MEC/British» programs; «Linguistic Programs» regulated by the regional «Plan of Plurilingualism», last amended in 2018; «Bilingual Programs» in semi-private schools) invites to reflect on how neoliberalism plays a role in the commodification of English language teaching and learning in these programs. Particularly, the article discusses how teachers participating in these programs position themselves towards their personal experiences teaching CLIL (Content and Language Integrated Learning) subjects in these bilingual programs. The analysis shows how these teachers are appropriating and resisting in some cases bilingualism as a neoliberal ideology and practice that reconfigures their professional identities as self-governing free subjects who must know English at all costs to compete in the highly commodified global market of English.